Pengembangan Model Latihan Lempar Lembing Melalui Permainan Fun Game Training Ekstrakulikuler Atletik SMA Negeri 1 Ketanggungan - Gilang, Meillenio Agung; Rumini, Rumini (Indonesian Journal for Physical Education and Sport, 2023)
Extracurriculars benefits can meet the movement needs of athletes, can introduce children to understand their talents, provide their skills, and can channel their physical needs into achievements. The purpose of this study is to develop a training model javelin throwing with extracurricular fun game training games athletics at SMA Negeri 1 Ketanggungan. This research is a development research, using the Research and Development method. From this study obtained results a percentage of 88% (Very Good), the results of the field tests showed the results of the percentage of 85% (Very Good), the expert lecturer validation test obtained the percentage results of 95% (Very Good), and the expert teacher validation test obtained with a percentage of 98% (Very Good). Based on the feasibility results obtained, the percentage results are 92% (Very Feasible). The researcher expects the javelin throwing training model through fun games game training can be developed and can be applied so that it inspires at every school